Actualization of the Principles of Accountability and Transparency in Reporting the Accountability of Program Activities at the Nusantara Student Dorm in Surabaya - Dava Ardian Santoso; Rediyanto Putra (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the actualisation of accountability and transparency principles in the programme activity accountability reporting practices of Asrama Mahasiswa Nusantara (AMN) Surabaya, a strategic national programme funded through the State Budget (APBN). Employing a qualitative single-case study design within an interpretive paradigm, data were gathered through in-depth interviews, passive participant observation, and document analysis involving five daily managers who hold strategic and operational roles in programme management. Analysis was guided by the interactive model of Miles and Huberman (1994) and triangulated across sources and techniques. Findings indicate that AMN Surabaya has implemented a systematic, multi-layered reporting mechanism encompassing annual work meetings, two-stage Terms of Reference (KAK) preparation, multi-party verification, structured accountability reports (LK and LPJ), and periodic reporting to multiple stakeholders. All four SAKIP indicators — performance planning, verification and control, periodic reporting, and evaluation and accountability — are substantively fulfilled. Transparency is enacted through a differentiated model that adjusts information coverage, channel, and format to the nature of each recipient. Consistent with Stewardship Theory, all five informants across different positions exhibited intrinsic motivation, moral burden, goal congruence, and beyond-compliance behaviour, affirming that the accountability mechanism functions not merely as procedural compliance but as a genuine stewardship of public trust. This study contributes to the public sector accounting literature by providing an operational-level perspective on the actualisation of good governance principles in state-funded dormitory programmes.